Kontribusi Adopsi Media Sosial dalam Menaikkan Penjualan dan Pengembangan Usaha Kecil dan Menengah di Indonesia - Henny Risnawati (Cakrawala Akuntansi & Manajemen, 2022)
Small and medium-sized enterprises (SMEs) are becoming an increasingly important economic factor in many developing countries, including Indonesia. Previous research shows that small businesses establish the concept of self-reliance. Even in times of economic hardship, small businesses are able to keep prices of national staples such as food and clothing low. In West Kalimantan, local SMEs produce a unique fabric called sasirangan, which has become the region's main product. As the use of IT infrastructure and platforms is usually concentrated in big cities such as the state capital of Pontianak, SMEs in the regions can rely on social media to promote their products. Therefore, this study aims to understand the attitudes of local SMEs towards using social media for commercial purposes. The sample size of this study includes 45 West Kalimantan SMEs in five districts outside the capital city of West Kalimantan. In this study, we used Partial Least Squares Structural Equation Modeling (PLS-SEM) to study the interaction between variables. The survey results show that small business entrepreneurs generally have a strong desire to use social media for commercial purposes. A more detailed description of the results and limitations of this study is available at the end of this document.